(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
This article reconstructs the judicial process followed in 1823 against Marcos Trujillo, an unlettered blacksmith who rendered services to the State in the times of the incipient República de Colombia (18211830). Faced with the few food rations he received for his work in the Maestranza de Pamplona and the separation from his family and his homeland, Trujillo decided to run away to be with his wife and children. This action constituted a crime of disobedience against the State, for which the Judge of the Villa de San Gil ordered that he be imprisoned and returned to the Maestranza to fulfill his obligations. On the way, Trujillo injured his foot and, according to witnesses, asked for a wooden stake to take his own life before returning to Pamplona. To the crime of disobedience, it was added the crime of unpatriotism and the crime of attempting to kill himself, based on the facts of injuring a foot his foot and asking for a wooden stake to kill himself. Despite the fact that the legislation of the República did not specifically establish attempted suicide as a violation of the law, Trujillo was tried and imprisoned for three crimes. The Colonial rule did punish the attempted "muerte propia" and the burning of the suicide’s corpse with the confiscation of property, and partly following the prerepublican religious tradition, both the Judge and the Prosecutor in the Trujillo case considered that the blacksmith did indeed violate the law on three grounds, although he was later pardoned.